Photoelectrochemical hydrogen generation at hybrid rGO-Sn3O4/SnO2 nanocomposite - da Costa Romeiro, Fernanda [UNESP]; Martins, Alysson Stefan [UNESP]; Costa e Silva, Beatriz [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Springer Nature, 2022)
This study investigates the photoelectrocatalytic water splitting at Sn3O4 and ternary rGO-Sn3O4/SnO2 heterostructure nanocomposite materials. The nanocomposite exhibited superior performance compared to Sn3O4, a result which was related to stronger absorption in the visible region, narrower band gap energy (1.8 eV), and higher photocurrent under both UV/Vis and visible light irradiation. The nanocomposite was also more efficient at photoexcited charge separation, as reflected in the enhanced H2 evolution. H2 production at the rGO-Sn3O4/SnO2 electrode reached a value that was twice as high as that of Sn3O4 under optimized photoelectrochemical conditions and UV/Vis irradiation. UV–Vis light induced a faster charge carrier on the nanocomposite’s surface due to the direct excitation of SnO2 and to posterior electron transfer to the reduced graphene oxide (rGO) followed by electron recombination at Sn3O4, as well as to electron excitation to the conduction band of Sn3O4 and further H2 evolution. This work provides an easy and low-cost method for obtaining Sn3O4-based materials for the production of clean energy. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Hydrogen evolution reaction; Photoelectrochemical properties; Reduced graphene oxide; Tin oxide